2012
DOI: 10.1021/mz300063g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Redox-Sensitive Shell Cross-Linked Nanoparticles for Controlled Release of Bioactive Agents

Abstract: Redox-sensitive shell cross-linked (SCL) poly­(2-(dimethylamino)­ethyl methacrylate)-block-polystyrene (PDMAEMA-b-PS) nanoparticles have been facilely fabricated by surfactant-free emulsion reversible addition–fragmentation chain transfer polymerization (SFE-RAFT), in which amphiphilic C12H25–PDMAEMA copolymers acted as stabilizers. 1H NMR, dynamic light scattering (DLS), and transmission electron microscopy (TEM) were applied to investigate the compositions and the morphologies of the resultant nanoparticles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…The average diameter determined by DLS is larger than that determined by TEM. This discrepancy is widely considered to be induced by the process of sample preparation and the difference of investigation method between DLS and TEM [22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…The average diameter determined by DLS is larger than that determined by TEM. This discrepancy is widely considered to be induced by the process of sample preparation and the difference of investigation method between DLS and TEM [22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, glutathione allowed the release of disulfide shell-crosslinked micelles [287]. Similar principles hold true for core-crosslinked micelles/nanoparticles/stars [288,289]. But, as already mentioned, this chemistry is seldom applicable for electrochemical switching.…”
Section: Chemical Redox For Self-assembled Systemsmentioning
confidence: 89%
“…Suda et al [288] reported the synthesis and characterization of a series of sulfonated star-hb polyimides (S-hb-PIs) without any crosslinking for use as proton exchange membranes. Sulfonated anhydride-terminated polyimides with different molecular weights (M w ¼ 59,000, 200,000 and 300,000 Da) based on monomer combination 1,4,5,8-naphthalene tetracarboxylic dianhydride/4,4 0 -diaminobiphenyl 2,2 0disulfonic acid (NTDA/BDSA) were synthesized using different molar ratios of BDSA:NTDA.…”
Section: Sulfonated Star Hyperbranched Polyimide For Pemfcmentioning
confidence: 99%
“…Commonly used core-forming hydrophobic polymers for drug delivery can be classified into the following groups: poly(propylene oxide) (PPO) as in Pluronics ®17 ; poly(esters) such as poly(lactic acid) (PLA) 18 and poly(ε-caprolactone) (PCL) 19, 20 ; poly(L-amino acids) such as poly(L-lysine) 21 ; and phospholipids and lipid-derivatives such as phosphatidyl ethanoloamine 22 . In addition, core-forming polymers such as polystyrene have been used in both in drug delivery systems 23 as well as fundamental research regarding polymer micelles 24 . These core-forming constituents cover a wide range of structural diversity and polarity for solubilizing a wide range of poorly water-soluble drugs.…”
Section: Structure and Compositionmentioning
confidence: 99%